Pain Relief and Efficacy of Surgical vs Nonsurgical Management of TMJ Disorders: A Systematic Review - D. Hima Madhuri; Athira Suresh; Parul Tikoo; Kumar Ankit; P. Subham; Aashish Kemmu (Journal of Pharmacy and Bioallied Sciences)
Temporomandibular disorders (TMDs) affect the jaw muscles and joints, with treatments ranging from surgery to nonsurgical methods like physiotherapy and medication. A systematic review of studies from January 2020 to May 2024 compared these treatments’ effectiveness in relieving pain and improving function. From 7,459 initial records, 18 studies were included, examining interventions like NSAIDs, low-level laser therapy, botulinum toxin A, and occlusal splints. Results varied, highlighting the need for personalized treatment and standardized outcomes to improve patient care.